Zrównoważony rozwój odnawialnych źródeł energii - Graczyk, Andrzej (Sustainable development of renewable energy sources, 2007)
Development of renewable energy sources is analyzed from the viewpoint of sustainable development principle. Its ecologic, social, and economic aspects are considered. The paper demonstrates that each of the aspects of the development in ąuestion may and has to be observed in a wider context, taking into account also indirect effects of the process. Some of the effects, both direct and indirect, may be appraised and expressed in economic terms. Second part of the paper presents legał provisions and their impact on sustainable development of energy based on renewable sources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 202-210